(untitled) (Communication & Society, 2017)
The economic crisis affecting Puerto Rico for the past years resulted in the migration of qualified talents (Brain Drain). This fact has been a public discussion taking covers in the media. This type of discussion is called risk communication. This work is based on the Cultivation theory, Framing and the Agenda Setting theory, by which the researchers developed a model that was applied through a survey, to 340 participants and it was analyzed under the PLS technique. The objective of the study is to analyze the impact of risk communication, through the framing and Agenda Setting on political, economic and social factors of brain drain in Puerto Rico. The results reflected that political and economic factors influence the interest to migrate out of the country, while social factors are influenced when the framed news presented in the media are present as moderating variables. This study contributes by presenting empirical evidence on the role of the media as influencers in the development of attitudes. The framing of the news and the projection of the information (setting) will induce an attitude that will result, in this case, in the interest of qualified talent to migrate out of the island